Ontologi Filsafat Pendidikan Islam: Studi di Pondok Pesantren Daar El Qolam - Chandra Nuruliana; Ahmad Fauzi; Subhan Subhan; Machdum Bachtiar (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2025)
Abstract: This research uses a qualitative approach with a library research method. The purpose of this research is to understand, analyse, and examine the understanding of the ontology of Islamic education based on existing theories and literature. This study reviews in depth the ontology of Islamic education philosophy, which is a branch of philosophy that discusses the nature of existence and reality in the context of Islamic education. This research highlights the ontological basis of Islamic education which is rooted in the Qur'an and Hadith as the main source. Islamic education is seen as an effort to form humans who have faith, morals, and have a balance between intellectual, spiritual, and social aspects. In this context, pesantren as one of the Islamic education institutions, such as Daar El Qolam Islamic Boarding School, becomes the object of study in the implementation of the ontology of Islamic education philosophy. The results showed that the philosophy of Islamic education is not only oriented towards the transfer of knowledge, but also aims to form humans with character and be able to answer the challenges of the times. Therefore, Islamic education must maintain basic principles such as diversity, skills, justice, and balance in order to continue to be relevant in the development of the modern world.Keywords: Ontology, Philosophy of Islamic Education, Islamic Boarding School Abstrak: Penelitian ini menggunakan pendekatan kualitatif dengan metode penelitian pustaka (library research). Tujuan penelitian ini adalah untuk memahami, menganalisis, dan mengkaji pemahaman ontologi pendidikan Islam berdasarkan teori dan literatur yang telah ada. Kajian ini mengulas secara mendalam ontologi filsafat pendidikan Islam, yang merupakan cabang filsafat yang membahas hakikat keberadaan dan realitas dalam konteks pendidikan Islam. penelitian ini menyoroti dasar ontologi pendidikan Islam yang berakar pada Al-Qur'an dan Hadis sebagai sumber utama. Pendidikan Islam dipandang sebagai usaha untuk membentuk manusia yang beriman, berakhlak, dan memiliki keseimbangan antara aspek intelektual, spiritual, dan sosial. Dalam konteks ini, pesantren sebagai salah satu lembaga pendidikan Islam, seperti Pondok Pesantren Daar El Qolam, menjadi objek kajian dalam implementasi ontologi filsafat pendidikan Islam. Hasil penelitian menunjukkan bahwa filsafat pendidikan Islam tidak hanya berorientasi pada transfer ilmu pengetahuan, tetapi juga bertujuan membentuk manusia yang berkarakter serta mampu menjawab tantangan zaman. Oleh karena itu, pendidikan Islam harus mempertahankan prinsip-prinsip dasar seperti keberagaman, keterampilan, keadilan, dan keseimbangan agar dapat terus relevan dalam perkembangan dunia modern.Kata Kunci: Ontologi, Filsafat Pendidikan Islam, Pondok Pesantren.